Properties of the Na(+)/K(+) pump current in small neurons from adult rat dorsal root ganglia - Hamada, Kanako (2003)
1. The present investigation was undertaken to characterize the Na(+)/K(+) pump current in small (⩽25 μm in soma diameter) dorsal root ganglion (DRG) neurons isolated from lumbar L4-6 segments of adult rats. 2. The Na(+)/K(+) pump current was identified as an ouabain-sensitive current during square voltage steps to membrane potentials between +40 and −120 mV, using the whole-cell patch-clamp technique in which Ca(2+) and K(+) channel currents and Na(+)/Ca(2+) exchange currents were minimized. The Na(+)/K(+) pump current was practically time-independent over the entire voltage range examined and exhibited a voltage-dependence; its current – voltage (I–V) relationship displayed a positive slope at potentials between −120 and 0 mV but nearly plateau levels at positive membrane potentials. 3. The concentration-dependent block of Na(+)/K(+) pump current (activated by 30 mM pipette Na(+)) by ouabain at concentrations between 0.1 μM and 5 mM was biphasic and was well described using a two-binding site model with dissociation constants for high- and low-affinity binding sites of 0.20 and 140.1 μM, respectively. The relative amplitude of the Na(+)/K(+) pump current produced by low- and high-affinity sites (probably α1β1 and α3β1 isozymes, respectively) was estimated to be 13 : 1 in the presence of 30 mM Na(+) in the pipette solution. 4. Additionally, the activation of Na(+)/K(+) pump current by pipette Na(+) at concentrations ranging from 5 to 100 mM also exhibited a biphasic concentration dependence which can be reasonably well fitted by assuming the existence of two isozymes having high and low affinities for Na(+) (6.7 and 67.6 mM, respectively). 5. Thus, the present investigation provides functional evidence to suggest that the Na(+)/K(+) ATPase comprises two functionally distinct isozymes as expected for α1β1 and α3β1 in rat small DRG neurons.